Facilities management as moderator in improving waste separation behaviour among households - Fitriyah, Razali; Dzurllkanian, Daud; Choong, Weng Wai; Wilson Rangga, Anthony Jiram; Noramirah Nabilah, Sulaiman; Raja Nurul Sakinah, Raja Syamsuddin (Emerald Publishing Limited, 2025)
This research focuses on the role of facilities management (FM) elements which are people who represent the household, and process, place and technology as the FM elements. The findings of this research include a list of suggestions to improve SSI implementation based on the FM elements. A waste separation behaviour model was established based on the findings, which was then further validated by experts in related fields. Design/methodology/approach: This paper explains how the process, place and technology elements of FM moderate and influence waste separation behaviour among households. A conceptual framework is proposed, grounded on the theory of planned behaviour (TPB), and a questionnaire survey was conducted to collect primary data from 900 eligible respondents among the residents of high-rise residential units in Malaysia’s capital city, Kuala Lumpur. SmartPLS software was used to analyse the structural equation model (SEM) of the conceptual framework developed to test the moderator’s effects. Findings: The findings show that the process, place and technology moderators significantly and positively affected the relationship between perceived behavioural control and waste separation behaviour. Process and technology moderators significantly and positively affect the relationship between moral norms and waste separation behaviour among households. This research focuses on the role of FM elements which are people who represent the household and process, place and technology as the FM elements. The findings of this research include a list of suggestions to improve Separation at Source Initiative (SSI) implementation based on the FM elements. A waste separation behaviour model was established based on the findings, which was then further validated by experts in related fields. Originality/value: This study implements the case of categorical moderator type and multiple constructs toward the relationships of formative indicators and contributes to knowledge regarding the analysis of moderator variables and structural equation modelling.